2005
DOI: 10.1029/2005gl024662
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of gravity waves induced by convection associated with Typhoon Rusa

Abstract: [1] Typhoon Rusa (2002) is simulated using a threedimensional mesoscale model (MM5), and the characteristics of gravity waves generated by convection associated with the typhoon are investigated. The gravity waves in the stratosphere propagate in two directions, northwestward and southeastward according to the convective bands propagating in the same directions, although the typhoon itself moves north-northeastward. Spectral analyses show that the inertio-gravity waves (IGWs) in the stratosphere generated by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 18 publications
7
64
0
2
Order By: Relevance
“…Climatologies of typhoon tracks can be found, for instance, in Knapp et al (2010), Hirata and Kawamura (2014), and references therein. The deep convection in tropical cyclones is a well-known source of convective GWs (e.g., Preusse, 2001;Kim et al, 2005Kim et al, , 2009 visible to various satellite instruments. In the numerical modeling study of Typhoon Saomai (2006), Kim and Chun (2010) estimate the absolute GWMF of typhoon-generated GWs at 25 km altitude for the period of 7-10 August 2006.…”
Section: Source Patterns Seen At 25 Km Altitudementioning
confidence: 99%
See 1 more Smart Citation
“…Climatologies of typhoon tracks can be found, for instance, in Knapp et al (2010), Hirata and Kawamura (2014), and references therein. The deep convection in tropical cyclones is a well-known source of convective GWs (e.g., Preusse, 2001;Kim et al, 2005Kim et al, , 2009 visible to various satellite instruments. In the numerical modeling study of Typhoon Saomai (2006), Kim and Chun (2010) estimate the absolute GWMF of typhoon-generated GWs at 25 km altitude for the period of 7-10 August 2006.…”
Section: Source Patterns Seen At 25 Km Altitudementioning
confidence: 99%
“…They found that there is strong convective excitation over the Gulf of Mexico and the Kuroshio Current for the Northern Hemisphere summer. These two regions are primary pathways for hurricanes and typhoons, respectively, and convection associated with hurricanes/typhoons can be a significant source of positive gravity wave momentum flux (GWMF) that is required to maintain large-scale circulation in the summer mesosphere (Kim et al, 2005;Kim and Chun, 2010). In addition, in the southern subtropics, regions of presumably convective GW excitation during the respective summer months were identified as well.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison with observations, Kim et al (2005) analyzed the characteristics of typhoon-generated GWs with the mesoscale model MM5. Numerical modeling study of convective GWs generated by Typhoon Rusa pointed out the importance of eastward propagating convective GWs in the middle latitudes as a significant source of positive momentum forcing in the summer mesosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research investigates the sources and mechanisms that generate gravity waves and the momentum flux (MF) they carry to the middle atmosphere. For example, Kim et al (2005) simulated 300-600-km waves above a hurricane in a model with 27-km horizontal resolution. The study presented here uses a near-cloud-resolving model with a 3-km horizontal spa-tial resolution and explicit microphysics so that smallerscale waves and their generation mechanisms may be resolved and investigated.…”
Section: Introductionmentioning
confidence: 99%